Associations Between Symptom Complexity and Acute Care Utilization Among Adult Advanced Cancer Patients Followed by a Palliative Care Service - Philip Pranajaya; Vincent Ho; Mengzhu Jiang; Vance Tran; Aynharan Sinnarajah (Current Oncology, 2025)
Among adult advanced cancer patients already accessing palliative care, symptoms can contribute to unplanned acute care utilizations, which can disrupt care and worsen patient outcomes. We examined how a novel symptom complexity algorithm, using patients’ ratings of the nine Edmonton Symptom Assessment System—Revised (ESAS-r) symptoms to assign “low”, “medium”, or “high” complexity, predicts acute care utilizations. This retrospective observational cohort study used electronic medical record data from the Durham Regional Cancer Centre in Ontario, Canada, comprising adult advanced cancer patients who completed at least one ESAS-r report between 1 January 2022 and 31 December 2023. We applied chi-squared tests, Kruskal–Wallis H tests, and multivariable binary logistic regressions to evaluate factors associated with higher odds of acute care utilization within seven and fourteen days of patients’ first ESAS-r reports after their first palliative care interaction. Of 559 included patients, 125 (22.4%) exhibited low complexity, 180 (32.2%) exhibited medium complexity, and 254 (45.4%) exhibited high complexity on their first ESAS-r report. In total, 61 (10.9%) patients accessed acute care within seven days and 108 (19.3%) patients accessed acute care within fourteen days of their first ESAS-r report. Controlling for sociodemographic and clinical covariates, compared to low-complexity patients, high-complexity patients had higher odds of acute care utilization within seven days (aOR = 2.83, 95% CI: 1.18–6.77), but not within fourteen days (aOR = 1.78, 95% CI: 0.97–3.28). Accordingly, as a clinical decision-making tool, ESAS-r symptom complexity may help identify patients who would benefit from more intensive follow-up and potentially reduce unnecessary acute care utilizations.